Efforts of Classroom Teacher Strategies and the Use of Learning Media on Students' Discipline Character - Anisa Alkamila; Haifaturrahmah; Muhammad Nizaar (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the role of classroom teacher strategies and the use of instructional media in shaping students’ disciplinary character through a Systematic Literature Review (SLR) approach. Literature sources were obtained from Google Scholar, ResearchGate, and the Directory of Open Access Journals (DOAJ), focusing on publications from 2020 to 2025. The findings reveal that teaching strategies involving exemplary behavior, habituation, supervision, and the implementation of reward and punishment systems are effective in fostering students’ discipline. The effectiveness of these strategies is further enhanced when integrated with engaging and contextual learning media such as educational videos, animations, and interactive digital tools. The synergy between teaching strategies and learning media strengthens the internalization of discipline values through meaningful learning experiences. However, research gaps were identified, including the limited number of empirical studies examining the synergistic relationship between teacher strategies and learning media, as well as the lack of longitudinal studies assessing long-term impacts. Furthermore, few studies have explored the integration of emerging technologies such as gamification and augmented reality in character education. Therefore, it is essential to develop an integrative learning model based on classroom teacher strategies and interactive digital media to reinforce students’ disciplinary character, contributing both theoretically to character education and practically to promoting a sustainable culture of discipline in elementary schools.